1973
DOI: 10.2134/agronj1973.00021962006500030005x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cutting Date on Digestibility and Intake of Irrigated First‐Crop Alfalfa Hay1

Abstract: Delayed cutting during the practical harvesting season of first‐growth forages raised in humid climates has resulted in a linear decline in the digestibility component of nutritive value. This study considered the effect of cutting date upon the digestibility and intake components of nutritive value of first growth alfalfa (Medicago sativa L.) raised under irrigated conditions at two altitudes in Utah and Montana. Duration of the study was 5 years with harvests occurring over ranges of 23 to 62 days. Intake an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Potential feed intake, which is estimated from cell-wall concentration and believed to have a more significant negative impact on animal utilization than reduced digestibility, is reduced with phenological advancement (Sanderson and Wedin, 1988;Troelsen and Campbell, I 959). Indeed, reduced intake may account for two-thirds of the total variability in animal performance (Byers and Ormiston, 1962;Anderson et al, 1973;Waldo and Jorgensen, 1981). Each day that spring growth of alfalfa progresses beyond the vegetative stage of development, a loss of potential feed intake amounting to 0.2: I g (forage wt.)…”
Section: Feed-quality Characteristics For Ruminantsmentioning
confidence: 99%
“…Potential feed intake, which is estimated from cell-wall concentration and believed to have a more significant negative impact on animal utilization than reduced digestibility, is reduced with phenological advancement (Sanderson and Wedin, 1988;Troelsen and Campbell, I 959). Indeed, reduced intake may account for two-thirds of the total variability in animal performance (Byers and Ormiston, 1962;Anderson et al, 1973;Waldo and Jorgensen, 1981). Each day that spring growth of alfalfa progresses beyond the vegetative stage of development, a loss of potential feed intake amounting to 0.2: I g (forage wt.)…”
Section: Feed-quality Characteristics For Ruminantsmentioning
confidence: 99%
“…The changes in forage quality between the April and May harvests showed an overall average decline of 0.71 g kg *1 d" 1 in CP and of 1.42 g kg 1 d" 1 in IVOMD, whereas the ADF rose by an average of 1.5 g kg" ' d~ '. The decline in CP contents (with serradella lines advancing from vegetative to flowering stage) was lower than the 2.0 to 2.8 g kg" 1 d"' reported by Buxton et al (1985) Anderson et al (1973) for alfalfa and by Buxton et al (1985) for alfalfa, birdsfoot trefoil, and red clover, although they used different in vitro digestibility methods. These slow reductions in the forage quality of the Ornithopus species, with advancing maturity, were also observed by Gladstones & Loneragan (1975) in Australia and Lapeyronie (1982) in northern Africa.…”
Section: Grasslandsmentioning
confidence: 56%
“…Crop maturity is a pattern of physiological changes. There is evidence that digestible dry matter and total digestible nutrients change from the first year of production to the second (Smith 1964: Baumgardt & Smith 1962: Anderson et al 1973. Sharratt et al (1987) found that lucerne responded differently to temperature, solar radiation, and wind speed as the stand aged.…”
Section: Qmentioning
confidence: 99%